1989
DOI: 10.1111/j.1467-8306.1989.tb00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Information Flows among Major Metropolitan Areas in the United States

Abstract: This study uses Federal Express Corporation data t o examine information flows among 48 large metropolitan areas in t h e United States. Set within t h e context of emerging quaternary location theory, three hypotheses are introduced t o explain t h e bases for information flows among metropolitan areas: information genesis, hierarchy of control, and spatial independence. Essential support is found for all three hypotheses. Supply considerations, rather than demand, are fundamental in information genesis; flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 35 publications
0
45
0
1
Order By: Relevance
“…The Wheeler and Mitchelson study (1989) showed that in the American urban system, New York City had by far the largest volume of net out-flows, and Kellerman (1992) suggested that "core countries" are called more frequently than "small periphery nations" (p. 1997: 176). In the present analysis, the international telephone flows resemble the patterns described by Wheeler and Mitchelson (1989) for the nation: that is, the nations with the largest net outflows of call (with negative numbers in Fig. 3) are the United States, followed by the United Kingdom, Hong Kong, Germany, and Canada.…”
Section: Hypothesis 2 Nations Can Be Organized Into a Hierarchy Basementioning
confidence: 67%
See 1 more Smart Citation
“…The Wheeler and Mitchelson study (1989) showed that in the American urban system, New York City had by far the largest volume of net out-flows, and Kellerman (1992) suggested that "core countries" are called more frequently than "small periphery nations" (p. 1997: 176). In the present analysis, the international telephone flows resemble the patterns described by Wheeler and Mitchelson (1989) for the nation: that is, the nations with the largest net outflows of call (with negative numbers in Fig. 3) are the United States, followed by the United Kingdom, Hong Kong, Germany, and Canada.…”
Section: Hypothesis 2 Nations Can Be Organized Into a Hierarchy Basementioning
confidence: 67%
“…The two geographic studies closest methodologically to the one described in this paper are the analyses of information flows among major metropolitan centers in the United States based on proprietary Federal Express data (Wheeler and Mitchelson, 1989;Mitchelson and Wheeler, 1994). In the 1989 paper, the authors analyzed a 48-by-48 metropolitan area matrix to identify patterns of common inter-city flows, confirming the hypotheses that a small number of command-and-control centers originate a large proportion of information flows, and that distance or the spatial distribution of destinations were unrelated to the volume of flows.…”
Section: Research Related To the Current Studymentioning
confidence: 99%
“…In economic geography, although economic actors and institutional factors still remain relevant (North 1989;Amin 2001;Hayter and Patchell 2011), evolutionary economic geography highlights the acquisition and production of knowledge as a fundamental characteristic and uses firms or individuals as the initial level of analysis (Simon 1955;Boschma and Frenken 2006;O'Hagan and Rice 2013). In urban planning, a vast literature has a long-standing interest in the location of corporate influence and power and includes scholars such as Goodwin (1965), Semple (1973), Wheeler and Mitchelson (1989), Rice and Semple (1993), and Tonts andTaylor (2010, 2013;see also O'Hagan and Rice [2013], for a detailed overview). The overall message in economic geography and urban planning highlights the importance of corporations as they generate spillover effects for local development (Storper 1997;Oinas 1997;Yeung, Poon, and Perry 2001) and they are commercial and information arbitrageurs (Tonts and Taylor 2010).…”
Section: University Of Bristolmentioning
confidence: 98%
“…J. Taylor and Thrift 1980;Tonts andTaylor 2010, 2013), China (Wu and Ning 2010;Pan and Xia 2014;Pan et al 2015), and Europe (Doma nski 2004; Bel and Fageda 2008;Doma nski and Gwosdz 2009). Although quaternary location research has occupied the vast majority of the literature by examining the geography of corporate functions, the distribution of high-level corporate board members, executives, and regional offices (Goodwin 1965;Semple 1973;Wheeler and Mitchelson 1989;Rice and Semple 1993;Tonts andTaylor 2010, 2013;Rice et al 2012;O'Hagan and Rice 2013), the literature has expanded and diversified into different areas (Rice and Lyons 2010). Even though such differentiation is not clearcut, they can be categorized into three subareas as the relationship between headquarters and corporate control; world cities; and local and regional development.…”
Section: Literature On Headquartersmentioning
confidence: 98%
“…How do people use geographic information, how does the information flow around an economy (Wheeler and Mitchelson, 1989) or society, how do children use maps (Freundshuh, 1990), and more specifically as Dymon (1989) notes 'Do we really know our map users'? However, there seems to be little crossfertilization into GIS of the wider cartographic debates on meaning and theory.…”
mentioning
confidence: 99%